Synthesis and pharmacological evaluation of novel potential ultrashort-acting beta-blockers - Mokrý, P; Zemanová, M; Csöllei, J; Racanská, E; Tumová, I (Die Pharmazie, 2003)
The basic relationship between chemical structure and pharmacological activity of eight newly developed potential ultrashort-acting beta-adrenergic blockers was evaluated. The compounds studied are derivatives of arylcarbonyloxyaminopropanols and were prepared by four-step synthesis. All the compounds evaluated showed weak antiisoprenaline (beta-adrenergic receptor blocking) activity and antiarrhythmic (antiouabain) activity.
Keywords: Propanolamines; techniky in vitro; spektroskopie infračervená s Fourierovou transformací; trachea; Guinea Pigs; propanolaminy; Spectrophotometry, Infrared; zvířata; Muscle, Smooth; Magnetic Resonance Spectroscopy; srdeční arytmie; svalová kontrakce; Myocardial Contraction; Adrenergic beta-Antagonists; Muscle Contraction; beta blokátory; Spectroscopy, Fourier Transform Infrared; Trachea; ouabain; Anti-Arrhythmia Agents; antiarytmika; isoprenalin; Adrenergic beta-Agonists; magnetická rezonanční spektroskopie; Ouabain; Isoproterenol; spektrofotometrie infračervená; hladké svalstvo; Heart Rate; Animals; Arrhythmias, Cardiac; srdeční frekvence; morčata; In Vitro Techniques; kontrakce myokardu; agonisté adrenergních beta-receptorů